Analysis of the Impact of Product and Advertising Innovation on Sales Volume - Desma Erica M Manik (LPPM STIE EKA PRASETYA, 2021)
This study aims to determine the effect of Product Innovation on Selling Volume at Gunung Teknik Stores, determine the effect of Advertising on Selling Volume at Gunung Teknik Stores, determine the effect of Product Innovation and Advertising on Selling Volume at Gunung Teknik Stores. The research methodology used is quantitative descriptive method. The type of data used in this study is quantitative data, that is data obtained in the form of numbers or numeric. The population in this study were all stores that had made purchases at the Gunung Teknik Store in 2019. Using the Slovin formula with an error rate of 5%, a total sample of 265 respondents was obtained. Data were analyzed using multiple linear regression analysis methods. The results showed that Product Innovation and Advertising had a positive and significant effect on Selling Volume at Gunung Gunung Store based on the results of the simultaneous hypothesis test.